The Relationship Between The Level Of Knowledge And Attitudes Of Adolescents With The Behavior Of The Three Basic Threats To Adolescent Reproductive Health (Triad Krr) In Grade Vii Students Of Smp Negeri 3 Candi Sidoarjo - Gladies Arnez Chory Cebryan Chory Febryan; Dwi Norma Retnaningrum Retnaningrum; Yuliyanik Yuliyanik (LPPM Widyagama Husada Malang, 2025)
Adolescence is a crucial transition period marked by major changes in physical, mental and social aspects, including the development of reproductive function. In Indonesia, teenagers are often faced with reproductive health challenges which are included in the KRR Triad concept, including sexuality, HIV/AIDS and drugs. This research aims to analyze the relationship between the level of knowledge and attitudes of teenagers towards their behavior in facing the KRR Triad, with a focus on class VII students at SMP Negeri 3 Candi Sidoarjo.The research design used was an analytical survey method using a cross-sectional approach. This research used respondents with a population of 285 people. Using the Slovin formula resulted in 74 respondents. The research instrument used was a questionnaire with validity tests and previous rehabilitation tests.The results of the research show that there is a significant relationship between the level of knowledge and attitudes towards adolescent behavior in the context of the KRR Triad, which is indicated by a statistical significance value of p < 0.05. The results of this study emphasize the importance of comprehensive reproductive health education as a means of increasing awareness and positive attitudes towards the KRR Triad. Recommendations for schools include improving reproductive health education programs, involving parents, teachers and health workers, as well as implementing interactive educational media for ongoing learning effectiveness so that it can help build healthy behavior patterns among teenagers.